Tunable negative differential resistance in a single cruciform diamine molecule with zigzag graphene nanoribbon electrodes. Issue 88 (7th September 2016) - Xie, Fang; Fan, Zhi-Qiang; Zhang, Xiao-Jiao; Liu, Jian-Ping; Wang, Hai-Yan; Long, Meng-Qiu
Abstract : We investigate the electronic transport properties of a single cruciform diamine molecule connected to zigzag graphene nanoribbon electrodes by using the non-equilibrium Green's function formalism with density functional theory. Abstract : We investigate the electronic transport properties of a single cruciform diamine molecule connected to zigzag graphene nanoribbon electrodes by using the non-equilibrium Green's function formalism with density functional theory. Negative differential resistance behavior can be discovered in the current–voltage curve of this molecular device. Then, one hydrogen atom in the molecule is replaced by an electron-donating group (–NH2 ) or an electron-withdrawing group (–NO2 ) in order to modulate the device's electronic transport properties. The results show the replacement of –NH2 on two different functionalized sites (R1 and R2) are all ineffective on the device's current–voltage characteristic. However, the replacement of –NO2 on R1 and R2 can enlarge the device's electron transport ability to different extents. More importantly, the original negative differential resistance behavior is also enhanced markedly. The above results offer us a new effective way to control the conductance and to modulate the negative differential resistance behavior in the single molecular device with zigzag graphene nanoribbon electrodes.